The female of Heteragrion icterops Selys, 1862 (Odonata: Heteragrionidae) with comments and key on the Brazilian females of Heteragrion group B - Vilela, Diogo Silva; Cordero-Rivera, Adolfo; Guillermo-Ferreira, Rhainer (Zootaxa, 2019)
The female of Heteragrion icterops Selys, 1862, incompletely mentioned in 1886, is described, illustrated, keyed and diagnosed based on specimens collected in Pará State, North Brazil. We also provide an identification key and diagnostic comments on other two Group B females occurring in Brazil: H. angustipenne Selys, 1886 and H. bariai De Marmels, 1989. Heteragrion icterops females can be distinguished from other female congeners by having the genital valves tips leveling the posterior margin of S10 and by the morphology of the intersternites, presenting a well-developed dorsal plate and lacking a posterior plate.